Dual Targeting of Multiple Myeloma Stem Cells and Myeloid-Derived Suppressor Cells for Treatment of Chemotherapy-Resistant Multiple Myeloma - Uckun, Fatih M. (Frontiers in Oncology, 2021)
Here we review the insights and lessons learned from early clinical trials of T-cell engaging bispecific antibodies (BsABs) as a new class of biotherapeutic drug candidates with clinical impact potential for the treatment of multiple myeloma (MM). BsABs are capable of redirecting host T-cell cytotoxicity in an MHC-independent manner to malignant MM clones as well as immunosuppressive myeloid-derived suppressor cells (MDSC). T-cell engaging BsAB targeting the BCMA antigen may help delay disease progression in MM by destroying the MM cells. T-cell engaging BsAB targeting the CD38 antigen may help delay disease progression in MM by depleting both the malignant MM clones and the MDSC in the bone marrow microenvironment (BMME). BsABs may facilitate the development of a new therapeutic paradigm for achieving improved survival in MM by altering the immunosuppressive BMME. T-cell engaging BsiABs targeting the CD123 antigen may help delay disease progression in MM by depleting the MDSC in the BMME and destroying the MM stem cells that also carry the CD123 antigen on their surface.